Preferential burial of permafrost‐derived organic carbon in Siberian‐Arctic shelf waters. Issue 12 (5th December 2014) - Vonk, Jorien E.; Semiletov, Igor P.; Dudarev, Oleg V.; Eglinton, Timothy I.; Andersson, August; Shakhova, Natalia; Charkin, Alexander; Heim, Birgit; Gustafsson, Örjan
Abstract The rapidly changing East Siberian Arctic Shelf (ESAS) receives large amounts of terrestrial organic carbon (OC) from coastal erosion and Russian‐Arctic rivers. Climate warming increases thawing of coastal Ice Complex Deposits (ICD) and can change both the amount of released OC, as well as its propensity to be converted to greenhouse gases (fueling further global warming) or to be buried in coastal sediments. This study aimed to unravel the susceptibility to degradation, and transport and dispersal patterns of OC delivered to the ESAS. Bulk and molecular radiocarbon analyses on surface particulate matter (PM), sinking PM and underlying surface sediments illustrate the active release of old OC from coastal permafrost. Molecular tracers for recalcitrant soil OC showed ages of 3.4–13 14C‐ky in surface PM and 5.5–18 14C‐ky in surface sediments. The age difference of these markers between surface PM and surface sediments is larger (i) in regions with low OC accumulation rates, suggesting a weaker exchange between water column and sediments, and (ii) with increasing distance from the Lena River, suggesting preferential settling of fluvially derived old OC nearshore. A dual‐carbon end‐member mixing model showed that (i) contemporary terrestrial OC is dispersed mainly by horizontal transport while being subject to active degradation, (ii) marine OC is most affected by vertical transport and also actively degraded in the water column, and (iii) OC from ICD settles rapidly and dominates surface sediments. Preferential burial of ICD‐OC released into ESAS coastal waters might therefore lower the suggested carbon cycle climate feedback from thawing ICD permafrost.